Longitudinal Test of Forgiveness and Perceived Forgiveness as Mediators between Religiosity and Marital Satisfaction in Long-Term Marital Relationships. Issue 4 (8th August 2018) - Rose, Andrew; Anderson, Shayne; Miller, Rick; Marks, Loren; Hatch, Trevan; Card, Noel
Abstract: Substantial research has found relations between religiosity and martial satisfaction. More longitudinal studies are needed to understand the inner-workings of this relationship. Over a four-year period, dyadic data from 331 married couples was used to test the longitudinal mediating effects of spousal forgiveness and partners' perceptions of spousal forgiveness between religiosity and marital satisfaction. Husbands' religiosity was associated with increases in wives' marital satisfaction but the measures of forgiveness were not significant mediators in this relationship. Wives' religiosity was predictive of lower levels of wives' perceptions of spousal forgiveness, which led to decreases in both wives' and husbands' marital satisfaction.